Oxide-doped sodium ion battery high-voltage positive electrode material and preparation method thereof
By doping Li and Ti elements into the nickel-ferromanganese layered hydroxide precursor of the sodium ion battery positive electrode material, a superlattice structure is constructed, which solves the problem of poor structural reversibility of the positive electrode material at high voltage, and significantly improves its high-voltage cycle stability and electrochemical performance.
Patent Information
- Application Number
- CN202510100818.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-22
AI Technical Summary
The positive electrode material of sodium ion batteries has poor structural reversibility at high voltages and has serious chemical machinery losses, resulting in poor circulation performance.
By doping Li and Ti elements in the nickel-ferromanganese layered hydroxide precursor, a superlattice structure is constructed, which inhibits the loss of lattice oxygen and the generation of transition metal vacancy clusters, and improves the high-voltage cycle stability of the material.
The high-voltage cycling stability of the positive electrode material of sodium ion battery is significantly improved, the capacity retention rate reaches 78.9% and 67.4% at 1C and 5C current density, respectively, and good electrochemical performance is maintained at high voltage.
Smart Images

Figure CN119873903A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high-voltage positive electrode materials for sodium ion batteries, and in particular to an oxide-doped high-voltage positive electrode material for sodium ion batteries and a preparation method thereof. Background Art
[0002] Sodium-ion batteries (SIBs) have emerged as an alternative to lithium-ion batteries (LIBs) in the field of large-scale energy storage. Compared with lithium, sodium resources are abundant, widely distributed, low-cost, and have higher electrode potential. From the performance point of view, sodium-ion batteries have better cost, low temperature, fast charging, and thermal stability. However, their main weakness is their low energy density. The positive electrode is a key component of LIBs and SIBs, and has an important impact on the cost, energy output, and cycle life of the battery. In SIBs based on ion embedding electrochemistry, cathode materials such as transition metal layered oxides, tunnel oxides, Prussian blue analogs (PBAs), and polyanionic compounds have attracted widespread attention from scholars.
[0003] Among them, transition metal layered oxides have become the preferred materials for compact cathode design due to their high theoretical capacity and voltage, fast electron conduction ability, optimized high-rate performance, and higher tap density compared to PBAs and polyanionic compounds, thus standing at the forefront of SIBs cathode research. In addition, due to the similarity in chemical structure between sodium ion layered oxides and lithium ion layered oxides, such as LiNi x Co y Mn 1-x-y As shown in Figure 2, the commonality of the two in production processes and process technologies makes it possible to share resources and greatly promotes the research, development and application of related materials. However, although the sodium ion layered oxide cathode has been widely studied in the past decade, the last step from the laboratory to the market is still challenging because of its unstable chemical properties in air and electrolyte, poor structural reversibility under high voltage, and chemical mechanical loss during repeated charge and discharge.
[0004] Transition metal oxides can be divided into P2 type and O3 type according to their structure. P2 type (space group is P63 / mmc) and O3 type (space group is ) The differences in crystal structure between the cathodes lead to their respective unique performance characteristics. Specifically, the sodium-poor P2-type cathode provides high discharge capacity but low initial charge capacity in a wide voltage region, which indicates an abnormal initial Coulombic efficiency (ICE); the sodium-rich O3-type cathode exhibits high charge / discharge capacity and less than 100% of the normal ICE, but has a slow Na +Diffusion kinetics and poor air stability. Compared with P2-type oxides, O3-type oxides have a narrower voltage range and lower energy density, and are not competitive enough in the field of high-performance battery materials.
[0005] Among the many studied ternary transition metal layered oxides, O3-NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2(NFM333) is a promising candidate for the cathode of sodium-ion batteries. The material significantly improves its commercial value by using cost-effective transition metal elements Fe and Mn. In addition, NFM333 exhibits a high conductivity of more than 130 mA hg -1 The 3D-SiO2 nanostructured carbon nanotubes have a respectable capacity (at 0.1C) and a relatively simple phase transition (O3-P3-P3-O3) in the voltage range of 2.0-4.0V.
[0006] Triggering the redox of lattice oxygen at high voltage is an effective strategy to improve the energy density of cathode materials. The redox of lattice oxygen allows more Na + Deintercalation and intercalation can contribute additional capacity compared to traditional transition metal redox reactions. Constructing a superlattice structure by doping Li elements in the layered oxide transition metal layer is a common method to activate lattice oxygen redox. At the same time, the incorporation of Li can reduce the JT effect of Fe and Mn elements, and its occupancy effect can also inhibit the irreversible migration of Fe elements. However, when the voltage is higher than 4.0V, the loss of lattice oxygen will cause an irreversible phase transition of O3-type oxides, which seriously damages the cycle performance of NFM333. The loss of lattice oxygen is caused by the generation of transition metal vacancy clusters and charged molecules O. Therefore, it is necessary to introduce other elements (such as Ti) to pin the vacancies and hinder the generation of clusters; at the same time, a transition metal-oxygen (TM-O) bond with high bond energy can be formed to reduce the generation of O2. Therefore, based on the nickel-iron-manganese hydroxide precursor that has been commercially prepared on a large scale, the direct use of Li / Ti co-doping method is expected to achieve the application of commercial NFM333 at high voltage, improve its energy density, and enhance competitiveness. Summary of the invention
[0007] The purpose of the present invention is to provide an oxide-doped sodium ion battery high-voltage positive electrode material and a preparation method thereof, which adopts a solid phase reaction method and achieves element doping by mixing a commercial nickel-iron-manganese layered hydroxide precursor with a metal oxide, thereby inhibiting the adverse phase change of the sodium ion layered oxide in the electrochemical reaction and the lattice oxygen loss during the charge and discharge process, and improving the high-voltage cycle stability.
[0008] To achieve the above object, the present invention provides a method for preparing an oxide-doped sodium ion battery high voltage positive electrode material, comprising the following steps:
[0009] S1, Na2CO3, (NiFeMn) 1 / 3 (OH)2, Li(OH)2·H2O and TiO2 are uniformly mixed and ground to obtain a premixed powder;
[0010] S2, drying the premixed powder in an oven to obtain dry powder;
[0011] S3, ball-milling the dried powder, and then pressing the powder into a tablet to obtain a disc;
[0012] S4, placing the disc in a high temperature tube furnace for high temperature sintering to obtain the oxide-doped sodium ion battery high voltage positive electrode material, denoted as Na 0.8 Ni 025 Fe 0.25 Mn 0.25 Li 0.1 Ti 0.2 O2.
[0013] Preferably, in S1, Na2CO3, (NiFeMn) 1 / 3 The dosage of (OH)2, Li(OH)2·H2O and TiO2 is: 0.8 Ni 025 Fe 0.25 Mn 0.25 Li 0.1 Ti 0.2 The stoichiometric ratios in O2 were calculated to obtain the calculated values. The amounts of Ni, Fe, Mn and Ti were calculated values, and the actual amounts of Na and Li were 5% more than the calculated values.
[0014] Preferably, in S2, the drying temperature is 50-80°C and the drying time is 12-14h.
[0015] Preferably, in S3, the rotation speed of the ball mill is 300-400 r / min, and the ball milling time is 2-3 h.
[0016] Preferably, in S3, the tableting pressure is 14-18 MPa.
[0017] Preferably, in S4, the specific operation during high temperature sintering is: using argon as protective gas, first heating to 400-500°C at a heating rate of 2-5°C / min, and keeping warm for 4 hours; then continuing to heat to 900-910°C at a heating rate of 6-10°C / min, and keeping warm for 24 hours.
[0018] The present invention provides an oxide-doped sodium ion battery high-voltage positive electrode material, which is prepared by adopting the above-mentioned method for preparing an oxide-doped sodium ion battery high-voltage positive electrode material.
[0019] Therefore, the present invention adopts the above-mentioned oxide-doped sodium ion battery high-voltage positive electrode material and the preparation method thereof, which has the following beneficial effects:
[0020] (1) The high-performance sodium ion battery cathode material of the present invention achieves metal doping by mixing metal oxides and commercial nickel-iron-manganese layered hydroxide precursors, thereby stabilizing the oxygen lattice and suppressing high-voltage phase transition, thereby optimizing the high-voltage cycle stability of the sodium ion battery;
[0021] (2) The sodium ion battery of the present invention has good cycle stability. After 200 cycles at a current density of 1C, the capacity retention rate is as high as 78.9%; after 1000 cycles at a current density of 5C, the capacity retention rate is as high as 67.4%.
[0022] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is an XRD diagram of NLT812 prepared in Example 1 of an oxide-doped sodium ion battery high-voltage positive electrode material and a preparation method thereof and NFM333 prepared in Comparative Example 1 of the present invention;
[0024] Figure 2 It is a scanning electron microscope and element distribution diagram of NLT812 prepared in Example 1 of an oxide-doped sodium ion battery high-voltage positive electrode material and a preparation method thereof of the present invention;
[0025] Figure 3 It is a scanning electron microscope and element distribution diagram of NFM833 prepared in Comparative Example 1 of an oxide-doped sodium ion battery high-voltage positive electrode material and its preparation method of the present invention;
[0026] Figure 4 The first cycle charge and discharge curve of the button cell assembled with NLT812 prepared in Example 1 of the present invention is at 0.1C;
[0027] Figure 5 The first cycle charge and discharge curve of the button cell assembled with NFM333 prepared in Comparative Example 1 of an oxide-doped sodium ion battery high voltage positive electrode material and its preparation method under 1C;
[0028] Figure 6 The present invention is an oxide-doped sodium ion battery high-voltage positive electrode material and preparation method thereof. The button cell assembled with NLT812 prepared in Example 1 and NFM333 prepared in Comparative Example 1 has a cycle number-specific capacity-coulombic efficiency curve at 1C;
[0029] Figure 7The present invention discloses an oxide-doped sodium ion battery high-voltage positive electrode material and a preparation method thereof. The cycle number-specific capacity-coulombic efficiency curve of a button cell assembled with NLT812 prepared in Example 1 and NFM333 prepared in Comparative Example 1 at 5C. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0031] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0032] Embodiment 1
[0033] A method for preparing an oxide-doped sodium ion battery high voltage positive electrode material comprises the following steps:
[0034] S1. According to Na 0.8 Ni 025 Fe 0.25 Mn 0.25 Li 0.1 Ti 0.2 Calculation of the stoichiometric ratios of Na2CO3, (NiFeMn) in O2 1 / 3 The amounts of (OH)2, Li(OH)2·H2O and TiO2, the amounts of Ni, Fe, Mn and Ti are calculated values, and the actual amounts of Na and Li are 5% more than the calculated values. 1 / 3 (OH)2, Li(OH)2·H2O and TiO2 are uniformly mixed and ground to obtain a premixed powder;
[0035] S2, drying the premixed powder in an oven at a temperature of 50° C. for 12 h to obtain a dry powder;
[0036] S3, the dried powder was placed in a ball mill for ball milling at a speed of 400 r / min for 2 h to obtain a gray-brown powder, which was then placed in a tablet press at a tableting pressure of 16 MPa to obtain a disc;
[0037] S4. The disc was placed in a high-temperature tube furnace for high-temperature sintering, with argon as the protective gas. The temperature was first raised to 450°C at a heating rate of 5°C / min and kept at that temperature for 4 hours; then the temperature was further raised to 900°C at a heating rate of 10°C / min and kept at that temperature for 24 hours to obtain the oxide-doped sodium ion battery high-voltage positive electrode material, denoted as Na 0.8 Ni 025 Fe 0.25 Mn 0.25 Li 0.1 Ti 0.2O2, represented by NLT812.
[0038] Embodiment 2
[0039] A method for preparing an oxide-doped sodium ion battery high voltage positive electrode material comprises the following steps:
[0040] S1. According to Na 0.8 Ni 025 Fe 0.25 Mn 0.25 Li 0.1 Ti 0.2 Calculation of the stoichiometric ratios of Na2CO3, (NiFeMn) in O2 1 / 3 The amounts of (OH)2, Li(OH)2·H2O and TiO2, the amounts of Ni, Fe, Mn and Ti are calculated values, and the actual amounts of Na and Li are 5% more than the calculated values. 1 / 3 (OH)2, Li(OH)2·H2O and TiO2 are uniformly mixed and ground to obtain a premixed powder;
[0041] S2, drying the premixed powder in an oven at a temperature of 60° C. for 12 h to obtain a dry powder;
[0042] S3, the dried powder was placed in a ball mill for ball milling at a speed of 300 r / min for 3 h to obtain a gray-brown powder, which was then placed in a tablet press at a tableting pressure of 16 MPa to obtain a disc;
[0043] S4. The disc was placed in a high-temperature tube furnace for high-temperature sintering, with argon as the protective gas. The temperature was first raised to 400°C at a heating rate of 5°C / min and kept at that temperature for 4 hours; then the temperature was further raised to 900°C at a heating rate of 10°C / min and kept at that temperature for 24 hours to obtain the oxide-doped sodium ion battery high-voltage positive electrode material, denoted as Na 0.8 Ni 025 Fe 0.25 Mn 0.25 Li 0.1 Ti 0.2 O2, represented by NLT812.
[0044] Embodiment 3
[0045] A method for preparing an oxide-doped sodium ion battery high voltage positive electrode material comprises the following steps:
[0046] S1. According to Na 0.8 Ni 025 Fe 0.25 Mn 0.25 Li 0.1 Ti 0.2Calculation of the stoichiometric ratios of Na2CO3, (NiFeMn) in O2 1 / 3 The amounts of (OH)2, Li(OH)2·H2O and TiO2, the amounts of Ni, Fe, Mn and Ti are calculated values, and the actual amounts of Na and Li are 5% more than the calculated values. 1 / 3 (OH)2, Li(OH)2·H2O and TiO2 are uniformly mixed and ground to obtain a premixed powder;
[0047] S2, drying the premixed powder in an oven at a temperature of 80° C. for 12 h to obtain a dry powder;
[0048] S3, the dried powder was placed in a ball mill for ball milling at a speed of 350 r / min for 2.5 h to obtain a gray-brown powder, which was then placed in a tablet press for tableting at a pressure of 16 MPa to obtain a disc;
[0049] S4. The disc was placed in a high-temperature tube furnace for high-temperature sintering, with argon as the protective gas. The temperature was first raised to 500°C at a heating rate of 5°C / min and kept at that temperature for 4 hours. The temperature was then further raised to 910°C at a heating rate of 10°C / min and kept at that temperature for 24 hours to obtain the oxide-doped sodium ion battery high-voltage positive electrode material, denoted as Na 0.8 Ni 025 Fe 0.25 Mn 0.25 Li 0.1 Ti 0.2 O2, represented by NLT812.
[0050] Comparative Example 1
[0051] Commercial NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The preparation method of O2 comprises the following steps:
[0052] A method for preparing an oxide-doped sodium ion battery high voltage positive electrode material comprises the following steps:
[0053] S1. According to NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Calculation of the stoichiometric ratios of Na2CO3 and (NiFeMn) in O2 1 / 3 The amount of (OH)2. 1 / 3 (OH)2 was mixed evenly and then ground to obtain a premixed powder;
[0054] S2, drying the premixed powder in an oven at a temperature of 50° C. for 12 h to obtain a dry powder;
[0055] S3, the dried powder was placed in a ball mill for ball milling at a speed of 400 r / min for 2 h to obtain a gray-brown powder, which was then placed in a tablet press at a tableting pressure of 16 MPa to obtain a disc;
[0056] S4. The disc was placed in a high temperature tube furnace for high temperature sintering, with argon as the protective gas, and the temperature was first raised to 450°C at a heating rate of 5°C / min and kept at that temperature for 4 hours; then the temperature was further raised to 900°C at a heating rate of 10°C / min and kept at that temperature for 24 hours to obtain NaNi 1 / 3Fe 1 / 3 Mn 1 / 3 O2, denoted as NFM333.
[0057] Experimental Test 1
[0058] according to Figure 1 As shown in the figure, the XRD results of NLT812 prepared in Example 1 and NFM333 prepared in Comparative Example 1 are basically consistent, but the peak position of NLT812 is shifted to the left as a whole compared with NFM333. This is because the introduction of Ti element and the reduction of Na element lead to an increase in the interlayer spacing. At the same time, the characteristic peak at 2θ=18.6° proves that Li / Ti co-doping successfully introduces a superlattice structure into the material.
[0059] Figure 2 The scanning electron microscope and element distribution map of NLT812 prepared in Example 1 are shown in FIG. Figure 3 The scanning electron microscope and element distribution diagram of NFM333 prepared in comparative example 1 are shown in FIG. Figure 2 and Figure 3 By comparison, it can be seen that the Ti element was successfully introduced into NLT812.
[0060] Experimental Test 2
[0061] In order to test the effect of Li / Ti co-doping on improving the high-voltage electrochemical performance of layered positive electrode oxide materials, NLT812 prepared in Example 1 and NFM333 prepared in Comparative Example 1 were assembled into half-cells in a glove box for testing. The specific steps are as follows:
[0062] NLT812 or NFM333 was used as the positive electrode, a metal sodium sheet was used as the negative electrode, the electrolyte was 1M NaClO4 in PC=100Vol% with 5% FEC, and a model 2032 button cell was used for battery assembly in an argon-protected glove box.
[0063] Under the current condition of 0.1C, the first cycle charge and discharge curves of button cells assembled with NLT812 and NFM333 are as follows: Figure 4 , Figure 5As shown in the figure, when NLT812 is charged to 4.4V, there is no obvious charge and discharge step like NFM333, which indicates that its structure does not change with Na + At the same time, the first cycle discharge capacity of NLT812 is as high as 161.39mA hg -1 , much higher than NFM333's 151.18mA hg -1 , which means that the stable superlattice constructed by doping Li elements successfully activated the reversible redox reaction mechanism of the oxygen lattice.
[0064] Under the current condition of 1C, the results of the cycle number-specific capacity-coulombic efficiency curve of the button battery assembled by NLT812 and NFM333 can be found in Figure 6 .Depend on Figure 6 It can be seen that the discharge capacity of NLT812 is as high as 119.84 mA hg at 1C current density. -1 , much higher than the 96mA hg of NFM333 -1 , and after 200 cycles, it still has a capacity retention rate of 77.69%.
[0065] Under the current condition of 5C, the results of the cycle number-specific capacity-coulombic efficiency curve of the button battery assembled by NLT812 and NFM333 can be found in Figure 7 .Depend on Figure 7 It can be seen that the discharge capacity of NLT812 is as high as 95.62mA hg at 5C current density. -1 , and after 1000 cycles, it still has a capacity retention rate of 69.20%, while the discharge capacity of NFM333 is 92.86mA hg -1 After 200 cycles, the structure collapsed significantly, and after 1000 cycles, there was almost no capacity. This shows that the stable superlattice structure constructed by Li / Ti co-doping has significantly improved the capacity and stability under high pressure compared with NFM333.
[0066] Therefore, the present invention adopts the above-mentioned oxide-doped sodium ion battery high-voltage positive electrode material and its preparation method, and achieves element doping by mixing a commercial nickel-iron-manganese layered hydroxide precursor with a metal oxide, thereby suppressing the adverse phase change of the sodium ion layered oxide in the electrochemical reaction and the lattice oxygen loss during the charge and discharge process, thereby improving the high-voltage cycle stability.
[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing an oxide-doped sodium ion battery high voltage positive electrode material, characterized in that: The following steps are involved: S1, Na2CO3, (NiFeMn) 1 / 3 (OH)2, Li(OH)2·H2O and TiO2 are uniformly mixed and ground to obtain a premixed powder; S2, drying the premixed powder in an oven to obtain dry powder; S3, ball-milling the dried powder, and then pressing the powder into a tablet to obtain a disc; S4, placing the disc in a high temperature tube furnace for high temperature sintering to obtain the oxide-doped sodium ion battery high voltage positive electrode material, denoted as Na 0.8 Ni 025 Fe 0.25 Mn 0.25 Li 0.1 Ti 0.2 O2.
2. The preparation method according to claim 1, characterized in that: In S1, Na2CO3, (NiFeMn) 1 / 3 The dosage of (OH)2, Li(OH)2·H2O and TiO2 is: 0.8 Ni 025 Fe 0.25 Mn 0.25 Li 0.1 Ti 0.2 The stoichiometric ratios in O2 were calculated to obtain the calculated values. The amounts of Ni, Fe, Mn and Ti were calculated values, and the actual amounts of Na and Li were 5% more than the calculated values.
3. The preparation method according to claim 1, characterized in that: In S2, the drying temperature is 50-80°C and the drying time is 12-14h.
4. The preparation method according to claim 1, characterized in that: In S3, the rotation speed of the ball mill is 300-400 r / min, and the ball milling time is 2-3 h.
5. The preparation method according to claim 1, characterized in that: In S3, the tableting pressure is 14-18 MPa.
6. The preparation method according to claim 1, characterized in that: In S4, the specific operation during high temperature sintering is: using argon as the protective gas, first increase the temperature to 400-500°C at a heating rate of 2-5°C / min, and keep it warm for 4 hours; then continue to increase the temperature to 900-910°C at a heating rate of 6-10°C / min, and keep it warm for 24 hours.
7. An oxide-doped sodium ion battery high voltage positive electrode material, characterized in that: The material is prepared by the method for preparing an oxide-doped sodium ion battery high-voltage positive electrode material as described in any one of claims 1 to 6.
Citation Information
Patent Citations
Preparation method of high-performance sodium-ion battery cathode material
CN108336334A
Sodium ion layered oxide positive electrode material for inhibiting slippage of transition metal layer and preparation method of sodium ion layered oxide positive electrode material
CN116425215A
High-voltage O3 type sodium ion battery positive electrode material and preparation method thereof
CN117174878A
O3 type layered positive electrode material with low Na content and preparation method thereof
CN118281197A
Low-nickel high-capacity sodium ion battery positive electrode material, preparation method and sodium ion battery
CN119092657A
Cited By
Sodium-ion battery layered oxide positive electrode material based on nitrogen-containing cerium source induced interface reconstruction and preparation method of sodium-ion battery layered oxide positive electrode material
CN121812539A